2010
DOI: 10.1080/03122417.2010.11689385
|View full text |Cite
|
Sign up to set email alerts
|

Earliest Evidence for Ground-Edge Axes: 35,400±410 cal BP from Jawoyn Country, Arnhem Land

Abstract: Evidence for the world's earliest stone tools dates to 3.4 million years ago and pre-dates the earliest known Homo species in eastern Africa. However ground-edged tools did not appear until the dispersal of cognitively fully modern Homo sapiens sapiens out of Africa. We report on the discovery of the earliest securely dated ground-edge implement in the world at Nawarla Gabarnmang (northern Australia). The fragment of ground-edge axe is sandwiched between four statistically indistinguishable AMS radiocarbon dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 18 publications
0
17
0
4
Order By: Relevance
“…Previous research reported ground-edge axes across much of northern Australia during the terminal Pleistocene, at Widgingarri 1 and Carpenter's Gap 1 and 3 in the Kimberley region of Western Australia (O'Connor 1999;O'Connor et al 2014), in western Arnhem Land at Malanangerr, Nauwalabila 1, Nawamoyn, and Nawarla Gabarnmang (Geneste et al 2010;Jones 1985;Schrire 1982;White 1967), and at Sandy Creek on Cape York (Morwood and Trezise 1989) (see Figure 1). These Australian ground-edge axes were invented locally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research reported ground-edge axes across much of northern Australia during the terminal Pleistocene, at Widgingarri 1 and Carpenter's Gap 1 and 3 in the Kimberley region of Western Australia (O'Connor 1999;O'Connor et al 2014), in western Arnhem Land at Malanangerr, Nauwalabila 1, Nawamoyn, and Nawarla Gabarnmang (Geneste et al 2010;Jones 1985;Schrire 1982;White 1967), and at Sandy Creek on Cape York (Morwood and Trezise 1989) (see Figure 1). These Australian ground-edge axes were invented locally.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the chronology of early axe production cannot be based solely on the recovery of whole axes, which are rare, and instead depends on the presence in well-dated excavations of flakes removed from the ground bevels of axes during the reshaping and repair of damaged and worn edges. This has been the basis for identifying axes dated to 35,000 BP in Australia (Geneste et al 2010). Suggestions of the presence of even older axes at Madjedbebe have been based on the presence of small flakes of volcanic material in sediments dated to more than 40,000 BP (Clarkson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Allen and Barton 1989;Bird et al 2002;Brockwell et al 2009Brockwell et al , 2011Clarkson et al 2017;David et al 2012;Delannoy et al 2013;Geneste et al 2010Geneste et al , 2012Gunn andWhear 2007a, 2007b;Gunn et al 2010aGunn et al , 2010bGunn et al , 2011Hiscock 1999;Hiscock et al 1992;Jones 1985;Meehan et al 1985;Roberts et al 1990;Schrire 1982;Shine et al 2013). At Nawarla Gabarnmang, a small piece of quartzite with charcoal lines was retrieved from buried sediments dated to 27,000-28,000 cal BP, one of the oldest dated painted images in Australia (David et al 2012).…”
Section: Recent Rock Art Research In Arnhem Landmentioning
confidence: 99%
“…Thus, in the first year of research (2010), we excavated Squares A and B. Unexpectedly for such shallow and well-stratified deposits, Square A revealed cultural deposits going down to 45,180 ± 910 cal BP, but deeper cultural sediments were evident in a very narrow crack (a phantomised fissure line) in the bedrock at the bottom of the square (see David et al 2011;Geneste et al 2010Geneste et al , 2012, indicating that nearby excavations in well-protected areas might reveal evidence of that earlier occupation. Square D was opened the following year to further track the early evidence of human occupation revealed in Square A, and Squares F+I+L+M were in part a continuation of this same tracking of old deposits across increasingly well-protected sectors of the site.…”
Section: The Archaeological Excavationsmentioning
confidence: 99%
“…The richness of the buried archaeological deposits dating from the earliest to the latest occupational levels, in particular the stone artefacts, makes Nawarla Gabarnmang a useful reference for understanding artefact characteristics in the central part of the Arnhem Land plateau (e.g. David et al 2011David et al , 2013Geneste et al 2010Geneste et al , 2012. Equally significant is Nawarla Gabarnmang's rock art; with 1391 paintings and stencils on the ceiling alone (i.e.…”
Section: Introductionmentioning
confidence: 99%